PENINGKATAN NILAI TAMBAH LABU MADU MENJADI E-TOURISM EDUKATIF DI DESA KLEBET - Dewi, Irma Dwi Puspita (Nindikayla Institute, 2023)
This Community Partnership Program activity aims to design an e-tourism site for an educational Ecological tourism village that promotes agricultural, plantation and livestock products in Klebet Village, Kemiri District, Tangerang Regency. There are 2 stages of implementing this activity, namely designing virtual e-tourism promotional media and how to apply social media in promoting an educational ecological tourism village in Klebet Village. The result of the service is the Klebet Village e-tourism website as an Educational Ecological Tourism Village which contains profile features village. The benefit of e-tourism sites for farmers and livestock breeders is that they apply e-tourism websites as a medium for online introduction. The conclusion of the service is that educational e-tourism is an alternative to increase added value for honey pumpkin farmers or Women Farming Groups (KWT) to achieve family welfare. With the results of this activity, it is hoped that it can improve the education of the public, students and university students in managing honey gourds as a practical learning medium for educational tourism which has an impact on improving the welfare of honey gourd farmers